Formula Ekstrak Mansoa alliacea dan Allamanda cathartica untuk Pengendalian Penyakit Busuk Batang pada Tanaman Kedelai - Made Susun, Ni Made Susun Parwanayoni; Darsini, Nyoman (Jurnal Fitopatologi Indonesia, 2023)
Mansoa alliacea and Allamanda cathartica Extract Formula for The Control of Stem Rot Disease on Soybean Plants The potential of flora biodiversity in Indonesia has not been optimally utilized as an environmentally friendly botanical pesticides, as well as reducing the use of synthetic pesticides on plants. The leaves of Mansoa alliacea and Allamanda cathartica have the potential as botanical pesticides because they were able to inhibit Athelia rolfsii, the causal agent of stem rot on soybean, in vitro. This research was conducted in the field scale to determine the optimal application of leaf extract of M. allicea dan A. cathartica that can affect disease development, the growth and productivity of soybean plants. Research stages included: extraction, extract formulation of M. allicea and A. cathartica , formula application on soybean plants, observation, and harvesting. The application of 1.5% leaf extract formula of M. alliacea and A. cathartica is recommended because it suppresses stem rot disease, increases plant growth and yields in the field.